Finding Dory - Novesky, Amy; Fejeran, Tony; Hashimoto, Satoshi 1973-; Disney Enterprises (1996-); Pixar Animation Studios Collection (Library of Congress) (New York Golden Books, 2016)
Dory has to make a trip across the ocean to get back to her mother and father
At head of title: Disney Pixar
2
Keywords: Fishes -- Juvenile fiction; Fishes; Marine animals -- Juvenile fiction; Marine animals; Memory -- Juvenile fiction; Memory; Parent and child -- Juvenile fiction; Parent and child; Fiction; Juvenile works